Subcellular Localization of Galloylated Catechins in Tea Plants [Camellia sinensis (L.) O. Kuntze] Assessed via Immunohistochemistry - Xu, Huanhuan; Wang, Ya; Chen, Yana; Zhang, Pan; Zhao, Yi; Huang, Yewei; Wang, Xuanjun; Sheng, Jun (Frontiers in Plant Science, 2016)
Galloylated catechins, as the main secondary metabolites in the tea plant, including (-)-epigallocatechin-3-gallate and (-)-epicatechin-3-gallate, comprise approximately three-quarters of all the tea plant catechins and have stronger effects than non-galloylated catechins, both on the product quality in tea processing and the pharmacological efficacy to human beings. The subcellular localization of galloylated catechins has been the primary focus of studies that assess biosynthesis and physiological functions. Classical histochemical localization staining reagents can not specifically detect galloylated catechins; thus, their subcellular localization remains controversial. In the present study, we generated a monoclonal antibody (mAb) against galloylated catechins, which can be used for the subcellular localization of galloylated catechins in the tea plant by immunohistochemistry. Direct ELISA and ForteBio Octet Red 96 System assay indicated the mAb could recognize the galloylated catechins with high specificities and affinities. In addition, tea bud was ascertained as the optimal tissue for freezing microtomic sections for immunohistochemistry. What’s more, the high quality mAbs which exhibited excellent binding capability to galloylated catechins were utilised for the visualization of them via immunohistochemistry. Our findings demonstrated that vacuoles were the primary sites of localization of galloylated catechins at the subcellular level.